ANALISIS WEB SECURITY HOLE MENGGUNAKAN METODE PENETRATION TESTING EXECUTION AND STANDARD (STUDI KASUS : UNIVERSITAS SINGAPERBANGSA KARAWANG) - Faizi, Zidan; ., Puwantoro; Ridha, Azhari Ali (Jurnal informasi dan komputer, 2023)
Web security is one of the main problems in today's digital era. In the face of security threats, Singaperbangsa University of Karawang (Unsika) needs to pay attention to the security of their information systems, especially on the website. Therefore, this research was conducted to analyze the security vulnerabilities of Unsika's website using the Penetration Testing Execution and Standard (PTES) method. This research aims to find and analyze security vulnerabilities on the Unsika website and provide recommendations for improving website security. The PTES method is used to test and analyze websites in terms of security, including vulnerability identification, penetration, and other security testing. The results showed that there were several security vulnerabilities on the Unsika website that could be exploited by attackers, After the scan was carried out, it was found that there was one vulnerability that had a high risk, five vulnerabilities with moderate risk, five vulnerabilities with low risk, and six vulnerabilities with informational risk. The recommendation given is to improve the security of the Unsika website by fixing the vulnerabilities that have been identified. In addition, it is also important to update and renew software and increase user awareness in managing and using information systems safely. In conclusion, this research proves that the PTES method can be used to find and analyze security vulnerabilities on the website. It is hoped that the results of this research can help Unsika in improving the security of their information systems, especially on the website.